IMPLEMENTASI DIVERSI PADA ANAK YANG MELAKUKAN TINDAK PIDANA PENCURIAN KENDARAAN BERMOTOR DI POLRESTA BANJARMASIN - Florentine Wilhemina Djeke (Badamai Law Journal, 2016)
Criminal act vehicle theft in law areas Polresta Banjarmasin more increasing. This improvement seen by loss reports received  Polresta Banjarmasin. The theft of vehicle in banjarmasin city most happened in residential areas of society, and parking areas. Criminal offender vehicle theft usually done in groups although individually. Unit investigator ranmor Sat Reskrim Polresta Banjarmasin made an efforts versioned in children who did criminal act of theft vehicle. Versioned  child development, coaching and mentoring children, proportionate, deprivation of liberty and punishment as the last effort and avoidance of retaliation juvenile justice law  aims to keep dignity of children, then child entitled get the special protects, especially law protect in system judisial.Unit investigator ranmor Sat Reskrim Polresta Banjarmasin made an versioned effort to child who did criminal act of theft vehicle versioned did because child is still underage and still a  Juvenille criminal justice system that was passed on july 30 th 2012 an effective on 32 st july 2014 legislation is a whole juvenile justice system. The process of resolving casses of children in conflict with the law began with the investigation to the stage of supervision after serving a punishment.Law juvenille justice system give the special protects to child according the principle of protection, fairness, discrininates, the best interest of the child, appreciation for the opinions of children, survival and growth.